PTC-174, a positive allosteric modulator of NMDA receptors containing GluN2C or GluN2D subunits. (15th August 2020) - Yi, Feng; Rouzbeh, Nirvan; Hansen, Kasper B.; Xu, Yuelian; Fanger, Christopher M.; Gordon, Earl; Paschetto, Kathy; Menniti, Frank S.; Volkmann, Robert A.
Abstract: NMDA receptors are ionotropic glutamate receptors that mediate excitatory neurotransmission. The diverse functions of these receptors are tuned by deploying different combinations of GluN1 and GluN2 subunits (GluN2A-D) to form either diheteromeric NMDA receptors, which contain two GluN1 and two identical GluN2 subunits, or triheteromeric NMDA receptors, which contain two GluN1 and two distinct GluN2 subunits. Here, we characterize PTC-174, a novel positive allosteric modulator (PAM) of receptors containing GluN2C or GluN2D subunits. PTC-174 potentiates maximal current amplitudes by 1.8-fold for diheteromeric GluN1/2B receptors and by > 10-fold for GluN1/2C and GluN1/2D receptors. PTC-174 also potentiates responses from triheteromeric GluN1/2B/2D and GluN1/2A/2C receptors by 4.5-fold and 1.7-fold, respectively. By contrast, PTC-174 produces partial inhibition of responses from diheteromeric GluN1/2A and triheteromeric GluN1/2A/2B receptors. PTC-174 increases potencies of co-agonists glutamate and glycine by 2- to 5-fold at GluN1/2C and GluN1/2D receptors, and NMDA receptor activation facilitates allosteric modulation by PTC-174. At native NMDA receptors in GluN2D-expressing subthalamic nucleus neurons, PTC-174 increases the amplitude of responses to NMDA application and slows the decay of excitatory postsynaptic currents (EPSCs) evoked by internal capsule stimulation. Furthermore, PTC-174 increases the amplitude and slows the decay of EPSCs in hippocampal interneurons, but has not effect on the amplitudes of NMDA receptor-mediated EPSCs in hippocampal CA1 pyramidal neurons. Thus, PTC-174 provides a useful new pharmacological tool to investigate the molecular pharmacology and physiology of GluN2C- and GluN2D-containing NMDA receptors. Graphical abstract: Image 1 Highlights: PTC-174 potentiates diheteromeric GluN1/2C, and GluN1/2D receptors by > 10-fold. PTC-174 also potentiates triheteromeric GluN1/2B/2D and GluN1/2A/2C receptors. PTC-174 is a partial antagonist of GluN1/2A and GluN1/2A/2B receptors. Agonist potencies of glutamate and glycine increase in the presence of PTC-174. PTC-174 modulates native GluN2D-containing NMDA receptors in distinct neuron types.